Syntheses of Pentanuclear Group 6 Iridium Clusters by Core Expansion of Tetranuclear Clusters with Ir(CO)2(η5-C5Me4R) (R = H, Me) - Randles, M.; Simpson, Peter; Gupta, V.; Fu, J.; Moxey, G.; Schwich, T.; Criddle, A.; Petrie, S.; MacLellan, J.; Batten, S.; Stranger, R.; Cifuentes, M.; et al. (2013)
Mixed molybdenum/tungsten tetrairidium and dimolybdenum/ditungsten triiridium clusters were prepared in high yield by cluster-core expansion of molybdenum/tungsten triiridium and dimolybdenum/ditungsten diiridium precursors, respectively, and were analyzed by a combination of spectroscopic, structural, and theoretical techniques. Tetrahedral molybdenum/tungsten iridium mixed-metal clusters undergo cluster-core expansion with iridium capping reagents to afford trigonal-bipyramidal MIr4(μ-CO)3(CO)7(η5-C5H5)(η5-L′), MoIr4(μ3-H)(μ-CO)2(μ-η1:η5-CH2C5Me4)(CO)7(η5-C5Me5) (possessing a μ-η1:η5-CH2C5Me4 ligand derived from a C−H bond activation of a C5Me5 methyl group), M2Ir3(μ-CO)3(CO)6(η5-C5H5)2(η5-L′), W2Ir3(μ-CO)4(CO)5(η5-C5H5)2(η5-C5Me4H), and Mo2Ir3(μ-CO)3(CO)6(η5-C5Me5)2 (L′ = C5Me5, C5Me4H). The spectroscopic, electrochemical, and spectroelectrochemical behavior of the clusters have been rationalized by time-dependent density functional theory.